Outcome of Tuberculosis Treatment: A Comparison between Alberta and Nicaragua - Narmin Kassam; Anne Fanning; Jose Ramon Cruz; Alejandro Tardencilla (Canadian Journal of Infectious Diseases)
OBJECTIVE: To measure the outcome of tuberculosis treatment in a low incidence, high income region, Alberta, and compare with an intermediate incidence, low income country with a model national tuberculosis program, Nicaragua.